Semiotics Study: Visual Analysis of the Wayang Character Rahwana in the Comic by R.A. Kosasih and Ardisoma - Rama Purwawicaksana Gedemukti; Djuli Djatiprambudi; Martadi Martadi; Anik Juwariyah (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2026)
Wayang is one of Indonesia's cultural products that has been passed down from generation to generation. Wayang stories, such as the Ramayana epic, are generally performed in the form of wayang kulit (leather puppet theatre) and are popular with the public because they are rich in meaning and moral values. As time has progressed, wayang has not only been presented in the form of performances, but has also been adapted into various media, one of which is comics. This study aims to reveal the representation of the character Rahwana in the Ramayana story adapted into comics and to compare the semiotic approaches in presenting the depth of this character from the perspectives of different comic artists. The method used is a descriptive qualitative approach with Charles Sanders Peirce's semiotic analysis model, which focuses on signs, objects, and interpreters. The data sources are Ramayana adaptation comics from two different comic artists. The results show that each comic artist has a distinctive adaptation style, both visually and conceptually, in describing the character of Rahwana. These differences are evident in the use of symbols, drawing styles, and the highlighting of certain characteristics that form diverse interpretations of the character. Thus, this study confirms that the adaptation process is not neutral but is influenced by the comic artists' creative interpretations. This research is expected to enrich the study of semiotics in visual arts and literature, particularly in the context of modern wayang.